Determination of rain cell size distribution for microwave link design in Malaysia - Khamis, Nor Hisham; Jafri, Din; Abd. Rahman, Tharek (IEEE, 2004)
In designing or planning for a microwave link, attenuation due to rain is often a major obstacle to overcome. Sometimes, a mitigation technique such as space diversity is also considered. However, a rain event occurring in an area is not constant. Rain does not distribute evenly in a region experiencing precipitation. This is especially true in tropical regions as rain has been found to be more convective in nature rather than widespread. Tropical regions also suffer heavier rainfall rates as compared to temperate regions. Important information are rain cell size and rain distribution inside a cell. Results from this study confirmed that the rain cell in Malaysia is highly convective and a rain cell with a center rainfall rate of 120 mm/hr has a diameter of about 1.2-1.5 km.